Anti-Diabetic and Haemodialysis Treatment Are Associated with Better Verbal Memory Performance - Othman, Zahiruddin; Ismail, Siti Zubaidah; Jamaluddin, Ruzita (Japan International Cultural Exchange Foundation, 2014)
Aim: The study aimed to evaluate verbal memory performance in end stage renal disease (ESRD) patients on maintenance haemodialysis (HD) and determine the relationship between the socio-demographic, clinical and biochemical characteristics of patients with verbal memory performance. Methods: A cross-sectional study of 91 ESRD patients on HD from December 2012 to May 2013 was conducted in nephrology unit, Hospital Sultanah Bahiyah and 3 private dialysis centres in Alor Setar, Kedah during the study period. Verbal memory performance and depression were assessed using the Malay version of the Auditory Verbal Learning Test (MVAVLT) and the Beck Depression Inventory (BDI) respectively during the first hour of HD procedures. Results: Older age, male gender and none/primary education were independently associated with worse verbal memory performance. In contrast, longer duration of HD and anti-diabetic treatment were associated with better verbal memory performance. Other factors, including depression, were not significantly associated with verbal memory performance. Conclusion: Anti-diabetic and HD treatment are associated with better cognitive function. Hence, this study suggests the importance of good diabetic control and regular maintenance HD to prevent cognitive impairment in ESRD patients